Influence of Protective and Risk Factors on Resilience among Family Caregivers of Schizophrenia Patients - Faizatur Rohmi; Dita Kurnia Sari; Arik Agung Setiawan (Journal Of Nursing Practice, 2025)
Background: Developing resilience among family caregivers of schizophrenia patients is challenging. Families must be able to identify risk factors and manage them to achieve a dynamic family situation and have the ability to survive while caring for schizophrenia patients. Protective factors interact with risk factors and create strength for families to be resilient in caring for people with schizophrenia. Results: T-statistics showed that there was an influence of family protective (p = 0.016) and family risk factors (p=0.003) on family caregivers’ resilience. Conclusions: Protective and risk factors of families with schizophrenia are the main resources in developing family caregivers’ resilience. To promote family health and effective adaptation to the schizophrenia long-term care, it is critical to improve family protective factors such as family functioning and social support and minimize family risk factors such as social stigma in schizophrenic families.